INFORMATION DISORDER & THE ONLINE’S GATEKEEPING MECHANISM STRUGGLE IN POST TRUTH ERA - roziana febrianita; Astri Wulandari (JCommsci - Journal Of Media and Communication Science, 2020)
Online journalistic practice in Indonesia has become a singular phenomenon in the digital era. Along with the rapid development of communication technology, the news portals in this country are also growing. The ease of access to any information; which is able to be accessed by anyone and anywhere has emerged to be one of many factors why online news sites tendecially being used as the main reference for any kind of information. Oppositely, there has been a wide spreading of misinformation, malinformation as well disinformation, which are circulated on social media and micro-blogging media. The concepts authors initiate in this research are the gatekeeping mechanism and disorder information. This has become the focal point of the paper to observe how the gatekeeping mechanism struggle with the occurrence. This paper method is qualitative, preserverving the interview data collecting technique. Informants in this paper are the editorial team of Liputan6.com and Detikcom. The conclusions of this article are : (a) Liputan6.com implemented traditional gatekeeping yet a gatewatching for the reader(s), Detikcom performing a processing journalism, (b) both media stated Information selection based on certain criteria, (c) Liputan6com expending SCTV East Java Bureau for disseminating the local news, Detikcom has representative in the back office in East Java for the local news, (d) both media having the awareness whether the selecting information leading to online news term’s and phenomenon nowadays. Keywords: Information Disorder, Gatekeeping Mechanism, Online News Portal, Post Truth Era, Online Journalism